2014
DOI: 10.1002/ejlt.201400047
|View full text |Cite
|
Sign up to set email alerts
|

Chemical changes in microwave heated vegetable oils

Abstract: The aim of this study was to investigate the influence of microwave heating on sunflower and corn oil in two types of microwave oven. The microwave ovens had the same output power and varied mainly in time of dissipation. The oil samples were heated for 90% and 70% of the total heating time by the two types of ovens, named as the first and the second oven, respectively, and the remaining time was dissipation pause. It was observed that greater dissipation pause in second microwave caused degradation of oil alm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(29 citation statements)
references
References 19 publications
4
23
2
Order By: Relevance
“…In the present study, formation of hot spots within the samples heated in multimode MW oven could explain the greater formation of COPs in edible oils with added cholesterol, as compared to treatments carried out in unimode MW oven. This is consistent with data reported by Kreps et al .…”
Section: Resultssupporting
confidence: 94%
“…In the present study, formation of hot spots within the samples heated in multimode MW oven could explain the greater formation of COPs in edible oils with added cholesterol, as compared to treatments carried out in unimode MW oven. This is consistent with data reported by Kreps et al .…”
Section: Resultssupporting
confidence: 94%
“…These results also confirmed Malheiro et al in virgin olive oils. But some authors determined two times lower tocopherol degradation in microwave‐heated oils than we did. Thus it appears that food nutrients (at least Vitamin E derivatives) are better preserved during frying and especially deep‐fat frying than they are during microwave heating.…”
Section: Resultscontrasting
confidence: 71%
“…In other types of microwave oven, this parameter can be at manufacture set to 25–30% of the total time, leaving more time for energy dissipation. Some authors found twice lower content of fatty acid hydroperoxides in oils heated with microwave oven adjusted with longer dissipation period of time.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, microwave oven applications showed to be harmful to vegetable oils, being possible to observe their deterioration in few minutes. Several reports highlight vegetable oils quality degradation, reduction in bioactive compounds and properties, fatty acids degradation, pigments destruction, sensorial changes, and color modifications, as well as physical and rheological changes [11][12][13][14][15][16][17][18][19][20]. In fact, comparatively to a conventional oven heating, microwave heating induces higher and faster oils deterioration [21][22][23].…”
Section: Introductionmentioning
confidence: 99%